Correction: Yu et al. Antimicrobial Resistance of Escherichia coli for Uncomplicated Cystitis: Korean Antimicrobial Resistance Monitoring System. Antibiotics 2024, 13, 1075 - Seong Hyeon Yu; Seung Il Jung; Seung-Ju Lee; Mi-Mi Oh; Jin Bong Choi; Chang Il Choi; Yeon Joo Kim; Dong Jin Park; Sangrak Bae; Seung Ki Min; KAUTII Investigators (Antibiotics)
In the original publication [...]